From Sacred to Commodity and Beyond: Colour and Values in India. (January 2016) - Jha, Sadan
A venture in a less traversed terrain of Indian scholarship, this article looks at the transformation in the value regimes that go into the making of colours in the Indian milieu. At one level, this study traces the sacredness imbued in colours and at another level the article delves into the genealogy that gives rise to a complex where colour, colonial investment in the economy of colours (with an aim at capitalizing colours as commodities), values and experiential dynamics enshrined in the imageries and practices associated with colours all come together. With these entanglements, the idea is to engage with the social fabrics and the politics of colours in the Indian milieu. In this rendering, the distinction between values and forms collapses giving us in turn a field of aesthetic experience. Mobilizing a wide range of registers (written as well as pictorial, archival as well as literary), this story is narrated with key rubrics, such as, ambiguous location of colour in the discourse on visuality, social and cultural life of colours and the manner in which Western science and modernity has influenced the values pertaining to colours. However, the core anxiety is parked on the relation between colour, aesthetic experience and the question of value.